Game Theory Applications in Logistics and Economy - Tuljak-Suban, Danijela (IntechOpen, 2018)
This book provides a wide range of examples of the uses of game theory, even in situations where such application may seem unsuitable. This book explores cooperative, competitive, leader-follower games and the free-rider problem - as well as games with the aim of maintaining friendships or team work. The reader will be presented with a wide range of practical applications of game theory.